Inovasi dan Dakwah: Analisis Majelis Taklim Tambena Ate di Lenteng Madura - Hasan, Amir (Jisab, 2023)
Majelis Taklim is currently developing not only in the form of lectures or tausiyah, but has been collaborated with religious music such as qosidahan, rebana, hadrah and others. However, it is still not enough to attract public attention. Majelis Taklim needs to make changes in the public space by having innovative activities that offer Islamic teachings. The results of this research that Majelis Taklim Tambena Ate provides a positive spiritual nuance towards efforts to build Muslim communities and minimize the culture of carok (fighting) which has become the custom of the Madurese people. Then, the existence of this Majelis Taklim, like the Majelis Maklim in general. However, there are five forms of innovation in da'wah activities which may not be available at the Majelis Taklim normally. The activity is in the form of boarding schools, umrah savings, umrah gifts, halaqoh and mayoran.